Addition of bevacizumab to gefitinib plus chemotherapy as first-line therapy in EGFR L858R mutate advanced non-small cell lung cancer patients - Lei, Lingli; Zhan, Xiang; Li, Jixian; Ding, Yi; Li, Jiaxin; Zhou, Fengge; Feng, Alei; Li, Xiaomei; Yang, Zhe (Frontiers in Pharmacology, 2025)
BackgroundFor advanced non-small cell lung cancer patients with the epidermal growth factor receptor L858R mutation, the efficacy of the combination of tyrosine kinase inhibitor (TKI) and chemotherapy is suboptimal. Currently, it is unclear whether the combination of bevacizumab, gefitinib, and chemotherapy could improve the survival.Materials and methodsData was retrospectively collected at Shandong Provincial Hospital between June 2019 and December 2022. The patients were divided into two groups, ATC group receiving bevacizumab, gefitinib, and chemotherapy, and TC group receiving gefitinib and chemotherapy. After propensity score matching (PSM), progression-free survival (PFS) and overall survival (OS) were calculated along with the objective response rate (ORR) and disease control rate (DCR).ResultsThe study enrolled 217 patients, 58 in the ATC group and 149 in the TC group, and was adjusted to 55 and 118 after PSM, respectively. Both the ORR and DCR were higher in the ATC group compared to the TC group (ORR: 76.4% versus 65.3%; DCR: 89.1% versus 80.1%). After 41.30 months of follow-up, the first-line PFS in the ATC group was significantly longer than in the TC group, while OS was not (PFS: 22.26 months versus 19.18 months, P = 0.02; OS: 42.18 months versus 39.42 months, P = 0.91). Univariate and multivariate analyses indicated that ATC treatment and the absence of brain metastases positively predict PFS, with no variables that dependently predict OS.ConclusionThe combination of bevacizumab, gefitinib, and chemotherapy significantly benefits patients with the L858R mutation in first-line PFS but not OS.